Reworking Sexual Assault Response on University Campuses: Creating A Rights-Based Empowerment Model to Minimize Institutional Liability - Ashley Hartmann (Washington University Journal of Law & Policy, 2015)
This Note offers an alternative way to handle sexual assault responses on university campuses by creating a rights-based empowerment model, which would minimize institutional liability and protect more students. All too often, by painting incomplete pictures of victims, the media perpetuates rape myths. These attitudes and beliefs are generally false but are widely and persistently held, and serve to deny and justify male sexual aggression against women. When combined with the reluctance of universities to address sexual assault where the students involved were acquaintances, more victims are hesitant to report sexual assault. This Note explores how federal statutes such as Title IX of the Educational Amendments of 1972 and the Jeanne Clery Disclosure of Campus Security Policy have influenced university responses to sexual assault. In conclusion, this Note argues that by reframing sexual assault response processes, the rights of both the victim and expected perpetrator can be better respected.
Keywords: sexual assault; Title IX of the Educational Amendments of 1972; Jeanne Clery Disclosure of Campus Security Policy; rights-based empowerment; campus rape